Stres in spoprijemanje s stresom v mladostništvu - Dolenc, Petra (Revija za elementarno izobraževanje, 2015)
Stress and Coping with Stress in Adolescence. Because of the many developmental changes in adolescence, young people are exposed to greater likelihood of experiencing stress. On the other hand, this period is critical for developing effective and constructive coping strategies. In the contribution, we summarize part of what is known about stress, stress responses and coping. Throughout, we focus on common stressful events among adolescents and emphasize the importance of dealing successfully with stressors in their daily lives. Finally, we highlight the most frequently used instruments to measure coping behaviour in youth and present an overview of the research findings on differences in coping among adolescents according to age and gender.
Keywords: stress; coping; adolescents; gender; age; measurement